Demographic profile of pregnant HIV-positive women in Postmasburg, South Africa - Kalonji, Kabasele Muboyayi Hubert (University of Limpopo (Medunsa Campus), 2011)
Background: South Africa hosts the largest number of pregnant HIV-positive women, accounting for almost 15% of the global total. Many amongst these HIV-positive pregnancies are unplanned and may be related to reproductive unmet needs, sexual risky behaviours, and/or community, contextual and individual factors that may determine and/or make these HIV-infected women to fall pregnant. The occurrence of an HIV-positive pregnancy in our region implies however the practice of unprotected sex, and is associated with the risk of reinfection with a different strain of HIV as well as with the risk of HIV transmission to an uninfected male partner and to the offspring. Knowing the demographic profile of HIV-infected women who become pregnant and experience parenthood as well as the circumstances of occurrence of their pregnancies is necessary for developing policies and interventions aimed at addressing the reproductive needs of this subpopulation, thus preventing HIV-positive unintended pregnancies as well as the horizontal and vertical transmission of HIV. Objectives: This study had three objectives. The first objective was to describe the demographic profile of pregnant HIV-positive women attending antenatal care (ANC) in public sector clinics in Postmasburg, South Africa. The second study objective was to determine the proportion of these pregnant HIV-infected women who were aware of their HIV-positive status prior to the occurrence of their current pregnancy. Lastly, the third objective sought to describe the circumstances of occurrence of their current pregnancy. Methodology: We used a quantitative descriptive design to collect data on 41 consecutive pregnant HIV-positive women who attended ANC at three public sector clinics in Postmasburg, from September to December 2010. Participants were administered a structured pre-tested questionnaire in their home language by trained interviewers. The study instrument was designed to collect data related to participants‘ socio-demographic characteristics, the time-period of HIV- v positive diagnosis relative to their current pregnancy, and the circumstances of occurrence of their current pregnancy. Results: The analyses of the study results showed that pregnant HIV-positive women attending ANC in Postmasburg were likely to be young (mean age, 27.71 ± 5.72 years), never married (56.10%), Afrikans (65.9%) and Setswana speakers (58.52%) of low socioeconomic status, with no or one child (65.85%). The majority of participants (63.4%) were from a predominantly informal settlement; 78% were unemployed while 61% were either devoid of any income or were living with Rands 500 or less. Sex mixing was common in the 15-19 years-old, involving 80% of respondents of this age category. Most of respondents (78.05%) became aware of their HIV-positive diagnosis during their current pregnancy that was unplanned in 73.17%. The study findings also revealed low levels of pregnancy intendedness (31.71%), hormonal contraceptives use (24.9%) and condoms uptake (34.15%), with high rates of condoms failure among users (87.12%). Respondents also reported other circumstances of occurrence of their current pregnancy, including, irregular condoms use (14.29% of condom users), partner refusal to use condom (10%), stopping contraceptives use because of side effects (50% of users), partner‘s pressure (12% of participants), coerced sex (2.4%) and having had sex under the influence of alcohol (2.4%). Conclusion: These results highlight the need for improving the reproductive health services that are offered to HIV-positive individuals. Integrating PMTCT and Family planning services, training health workers in issues related to the reproductive rights and reproductive health of HIV-infected individuals, systematically offering HIV counseling and testing to women of childbearing age who come into contact with health facilities for any reason and adequately informing HIV-positive women of childbearing age about available reproductive options, planned conception and safer motherhood, are necessary for preventing unintended HIV-positive pregnancies as well as the horizontal and vertical transmission of HIV.
Thesis (MPH)--University of Limpopo (Medunsa Campus), 2011.
Keywords: HIV; HIV infections